Nutrient and fatty acid composition of cultured and wild caught gold-spot mullet Liza parsia (Hamilton, 1822) - Syama Dayal, J.; Ambasankar, K.; Jannathulla, R.; Kumaraguruvasagam, K. P.; Kailasam, M. (Indian Journal of Fisheries, 2019)
The gold-spot mullet, Liza parsia (Hamilton, 1822) is a common mullet species that constitutesÂ year round thriving fishery in the shallow coastal waters, estuaries, mangrove swamps and brackishwater lakes along the coast of India. Nutrient and fatty acid composition were analysed in cultured and wild caught Â L. parsia of different size groups. Fish were cultured with formulated pelleted feed in brackishwater pond at Nagayalanka (15.9450 N; 80.9180E), Andhra Pradesh, India. Wild samples of L. parsia were caught from the same region near Â Krishna River. The fishes were categorised into four size groups (<50 g, 50-100 g, 101-150 g and >150 g) from both sources. The moisture and ash content were higher (p<0.05) in wild fishes (75.85 and 1.39%) compared to cultured ones (72.96 and 1.29%). Cultured L. parsia had higher (p<0.05) crude lipid (2.12-8.73%) across all size groups compared to wild group which recorded crude lipid in the range of 0.67-3.10%. However, no significant change was observed for crude protein between wild and cultured fish. The quantities (mg 100 g-1 of fish muscle) of 18:2n-6 fatty acids were significantly (p<0.05) higher by 12 fold in farmed fish, whereas 20:4n-6 was higher (p<0.05) by two times in captive L. parsia. Significant (p<0.05) difference was observed in docosahexaenoic acid (DHA) content between the cultured and wild fish (108.60 and 89.90 mg 100 g-1, respectively) but not in eicosapentaenoic acid (EPA) (110.59 and 115.03 mg 100 g-1 respectively). The consumption of 100 g L. parsia fish which was above 100 g size of both wild and farmed could meet per day (250 mg) dietary needs of EPA and DHA. Keywords: DHA, EPA, Fatty acids, Liza parsia, Mullet, Nutrients